Consequences of Untreated Posttraumatic Stress Disorder Following War in Former Yugoslavia: Morbidity, Subjective Quality of Life, and Care Costs - Priebe, Stefan (Array, 2009)
Aim. To assess long-term mental health outcomes in people who suffer from war-related posttraumatic stress disorder (PTSD) but do not receive appropriate treatment. Methods. We interviewed 264 subjects from former Yugoslavia, who lived in Croatia, Serbia, Germany, and the United Kingdom. All of them had suffered from PTSD at some point following the war, but never received psychiatric or psychological treatment. The interviews took place on average 10.7 ± ; 3.0 years after the war-related trauma. Outcomes were current PTSD on the Clinician Administered PTSD Scale for Diagnostic and Statistical Manual of Mental Disorders-IV, subjective quality of life (SQOL) on the Manchester Short Assessment of Quality of Life, and care costs. Socio-demographic characteristics, the level of traumatic war-events, and aspects of the post-war situation were tested for association with outcomes. Results. Current PTSD was diagnosed in 83.7% of participants, the mean SQOL score was 4.0 ± ; 0.9, and mean care costs in the last 3 months exceeded € 1100 in each center. Older age, more traumatic war-events, lower education, and living in post-conflict countries were associated with higher rates of current PTSD. Older age, combat experience, more traumatic war-events, being unemployed, living alone, being housed in collective accommodation, and current PTSD were independently associated with lower SQOL. Older age and living in Germany were linked to higher costs of formal care. Conclusion. People with untreated war-related PTSD have a high risk of still having PTSD a decade after the traumatic event. Their SQOL is relatively low, and they generate considerable care costs. Factors that have been reported as influencing the occurrence of PTSD also appear relevant for recovery from PTSD. Current PTSD may impair SQOL independently of social factors.